2018
DOI: 10.3390/ijms19030790
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal or Not Virucidal? That Is the Question—Predictability of Ionic Liquid’s Virucidal Potential in Biological Test Systems

Abstract: For three decades now, ionic liquids (ILs), organic salts comprising only ions, have emerged as a new class of pharmaceuticals. Although recognition of the antimicrobial effects of ILs is growing rapidly, there is almost nothing known about their possible virucidal activities. This probably reflects the paucity of understanding virus inactivation. In this study, we performed a systematic analysis to determine the effect of specific structural motifs of ILs on three different biological test systems (viruses, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 67 publications
(110 reference statements)
2
42
0
Order By: Relevance
“…In 2018, Sommer et al [ 186 ] performed a systematic analysis of 27 different ILs, with the aim to determine their effect toward viruses, bacteria and enzymes (two non-enveloped, one enveloped virus: P100, MS2 and Phi6, two Gram negative and one Gram positive bacteria: E. coli , P. syringae and L. monocytogenes , one enzyme: Taq DNA polymerase.…”
Section: Usefulness Of Ionic Liquids In Medicinementioning
confidence: 99%
“…In 2018, Sommer et al [ 186 ] performed a systematic analysis of 27 different ILs, with the aim to determine their effect toward viruses, bacteria and enzymes (two non-enveloped, one enveloped virus: P100, MS2 and Phi6, two Gram negative and one Gram positive bacteria: E. coli , P. syringae and L. monocytogenes , one enzyme: Taq DNA polymerase.…”
Section: Usefulness Of Ionic Liquids In Medicinementioning
confidence: 99%
“…In this respect, it has been found that some ILs can stop the replication cycle of the human immunodeficiency virus (HIV) by inhibiting the function of HIV-integrase, which is an important enzyme in the virus replication cycle (Maddali et al 2011 ). The viricidal activity of ILs has been proven in few other cases, but the associated mechanisms need further investigations (Kumar and Malhotra 2008 ; Sommer et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This includes active substances such as potassium peroxymonosulfate, ethoxylated nonylphenol, Triclosan, chlorhexidine diacetate, Quaternary Ammonium Compounds (QACs) such as benzalkonium chloride or ionic liquids, Chloramine-T and monochloramine, which have drawn the interest of research groups [41,169,171,173,174,175,176,177,178]. More information regarding the regulation of these substances is included in the supplemental material of this review (see Table S4).…”
Section: Legal Regulation Of Disinfectants Currently Used In Food mentioning
confidence: 99%